A Rare Case of Cardiac Metastatic Uterine Intravenous Leiomyomatosis - Wu, Xun; Li, Feng; Iroegbu, Chukwuemeka Daniel; Fan, Chengming; Song, GuoBao (Frontiers in Cardiovascular Medicine, 2022)
Intravenous leiomyomatosis (IVL) is a special type of uterine leiomyoma, combined with intracardiac invasion is very rare. Although leiomyomas are histologically benign, intracardiac metastasis may lead to circulatory failure and even death. Here, we report a 55-year-old woman who was found to have invaded the ovarian, internal iliac vein and inferior vena cava after the discovery of a tricuspid chordal tumor. The patient successfully underwent tricuspid chordectomy and tricuspid chordectomy. A cusp valvuloplasty and resection of the inferior vena cava, common iliac vein, uterus, and bilateral appendages were performed 4 months later. To our knowledge, this is the first reported case of this combination.